The influence of hospital volume upon clinical management and outcomes of esophageal achalasia: an English national population-based cohort study. Issue 9 (9th July 2018) - Wiggins, T; Markar, S R; MacKenzie, H; Faiz, O; Zaninotto, G; Hanna, G B
Summary: Management of achalasia is potentially complex. Previous studies have identified equivalence between pneumatic dilatation and surgical cardiomyotomy in terms of clinical outcomes. However, previous research has not investigated whether a management strategies and outcomes are different in high-volume achalasia centers. This national population-based cohort study aimed to identify the treatment modalities utilized in centers, which regularly manage achalasia and those which manage it infrequently. This study also assessed rates of re-intervention and complications to establish if a volume–outcome relationship exists for the management of achalasia in England. In this study, the Hospitals Episode Statistics database was used to identify all patients treated for achalasia in England from 2002 to 2012. Primary treatment was defined as surgical cardiomyotomy, sequential pneumatic dilatation, or botulinum toxin therapy. Primary outcome measure was reintervention. Centers were divided into regular achalasia centers (≥5.7 cases per annum) and infrequent achalasia centers (<5.7 cases per annum), and were analyzed according to tertiary cancer center status. In total, there were 7, 487 patients treated for achalasia. Out of 1, 947 cases (26%) were treated in regular achalasia centers, with 5, 540 (74%) treated in infrequent centers. In binary logistic regression modeling regular centers treated a similar proportion of patients with primary surgical cardiomyotomy (OR: 1.11 (95% CI 0.98–1.27)) and had similar rates of re-intervention to infrequent achalasia centers (HR: 1.03 (0.94–1.12)). RA-CUSUM analysis demonstrated no relationship between total hospital volume and reintervention rates. Tertiary cancer centers treated more achalasia patients with primary surgical cardiomyotomy (OR: 1.51 (95% CI 1.31–1.73)) but there was no significant difference in reintervention rates (OR: 1.05 (95% CI 0.95–1.16)). In conclusion, this analysis failed to demonstrate a volume–outcome relationship in the management of achalasia in England. This study highlights that achalasia is treated infrequently by the majority of centers.